Coastal plain stratigraphy records tectonic, environmental, and human habitability changes related to sea-level drawdown, 'Upolu, Sāmoa. Issue 2 (27th February 2017) - Kane, Haunani H.; Fletcher, Charles H.; Cochrane, Ethan E.; Mitrovica, Jerry X.; Habel, Shellie; Barbee, Matthew
Abstract: Coastal plain stratigraphy is often over looked in paleo–sea-level reconstructions because carbonate sediments do not precisely constrain former sea level. Pacific Island sedimentology provides an invaluable record of geomorphic and environmental consequences of coastal evolution in response to changes in sea level and local tectonics. A series of coastal auger cores obtained from eastern ʻUpolu reveal a subsurface carbonate sand envelope predominately composed of coral and coralline algae derived from the reef framework. Coupling the sedimentological record with geophysical models of Holocene sea level, we identify a critical value (0.3–1.0 m) during the falling phase of the sea-level high stand (1899–2103 cal yr BP) that represents the transition from a transgressive to a regressive environment and initiates coastal progradation. Correlating the critical value with time, we observe nearly a millennium of coastal plain development is required before a small human population is established. Our findings support previous studies arguing that Sāmoa was colonized by small and isolated groups, as post–mid-Holocene drawdown in regional sea level produced coastal settings that were morphologically attractive for human settlement. As future sea level approaches mid-Holocene high stand values, lessons learned from Pacific Island sedimentological records may be useful in guiding future decisions related to coastal processes and habitat suitability.